Histological alterations following fine‐needle aspiration for parathyroid adenoma: Incidence and diagnostic problems. Issue 6 (19th March 2021) - Hirokawa, Mitsuyoshi; Suzuki, Ayana; Higuchi, Miyoko; Hayashi, Toshitetsu; Kuma, Seiji; Miya, Akihiro; Miyauchi, Akira
Abstract : This study aimed to clarify the histological alterations following fine‐needle aspiration for parathyroid adenoma and discuss the occurrence of diagnostic problems. Among the 392 patients with parathyroid adenoma who underwent resection, fine‐needle aspiration was performed for 21 (5.1%) parathyroid adenoma nodules. Histological findings that were significantly more frequent in cases that underwent fine‐needle aspiration were considered histological alterations following fine‐needle aspiration for parathyroid adenoma, including the following six findings: thick fibrous capsule (71.4%), multilayered fibrous capsules (14.3%), capsular pseudo‐invasion (42.9%), fibrous bands (57.1%), hemosiderin deposition (14.3%), and tumor implantation (14.3%). Eighteen parathyroid adenoma nodules (85.7%) exhibited one or more of the six findings. Tumor cells and adipocytes entrapped within the thick fibrous capsule were occasionally observed. The fibrous bands were frequently connected to the thick fibrous capsule. The number of passes, duration between fine‐needle aspiration and resection, tumor size, and purpose of fine‐needle aspiration were not related to the incidence of histological findings. Because of the histological alterations following fine‐needle aspiration for parathyroid adenoma that can be easily mistaken for signs of atypical adenoma or parathyroid carcinoma, we recommend that the six findings be excluded from pathological findings indicating atypical adenoma or parathyroid carcinoma in patients with preoperative fine‐needle aspiration.